Talent identification and development in soccer since the millennium - Williams, A. M.; Ford, P. R.; Drust, B. (Journal of Sports Sciences, 2020)
At the turn of the millennium, a review paper was published in this journal on talent identification and development in soccer (Williams & Reilly, 2000). In the current paper, we assess progress made in this field over the last twenty years relative to the areas for future research highlighted in the original review. We evaluate developments in light of the calls made by Williams and Reilly to: a) undertake more multidisciplinary rather than mono-disciplinary research; b) embrace longitudinal rather than cross-sectional research designs; c) expand the research base on female football; and, d) better identify the subjective criteria used by scouts when selecting one player over another for entry into a formalised training environment. The body of mono-disciplinary research on this topic continues to expand, and progress has been made in publishing multidisciplinary, prospective, longitudinal data sets, along with advanced statistical modelling procedures, as well as in identifying the experiential criteria used by scouts. We found some variables in these studies have predictive value from adolescence to adult performance level in soccer. We present suggestions for future research to enhance knowledge and understanding of the best practices underpinning the identification and development of future generations of professional players.